Antimicrobial Resistance Through the Lens of One Health in Ethiopia: A Review of the Literature Among Humans, Animals, and the Environment. (June 2022) - Fujita, Ayako Wendy; Werner, Kaitlyn; Jacob, Jesse T.; Tschopp, Rea; Mamo, Gezahegne; Mihret, Adane; Abdissa, Alemseged; Kempker, Russell; Rebolledo, Paulina A.
Highlights: High antimicrobial resistance (AMR) rates in S. aureus and gram-negative pathogens High rates of AMR in humans, animals, and environment Few studies assess AMR across multiple One Health sectors in Ethiopia One Health approach should be integrated into AMR surveillance Abstract: Objectives: We aimed to review and describe antimicrobial resistance (AMR) prevalence in humans, animals, and the environment in Ethiopia. Methods: We conducted a structured review of literature on AMR in humans, animals, and the environment in Ethiopia from 2016–2020. We reported the pooled prevalence of AMR of bacterial pathogens in all 3 sectors. Results: We included 43 articles in our review. Only 5 studies evaluated AMR across multiple sectors. The most common bacteria in humans were Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus . High prevalence of resistance to third-generation cephalosporins, fluoroquinolones, and sulfamethoxazole-trimethoprim were seen in gram-negative organisms, often with >50% prevalence of resistance. Highest resistance rates were seen in humans, followed by environmental isolates. Salmonella spp. exhibited higher rates of resistance than previously reported in the literature. We found methicillin-resistant S. aureus (MRSA) in approximately half of S. aureus from the environment and a third from human isolates. Few studies evaluated AMR across all 3 sectors. Conclusion: Our review demonstrated high prevalence of AMR among bacteria in humans, animals, and the environment in Ethiopia. Integrating a One Health approach into AMR surveillance as part of Ethiopia's national surveillance program will inform future implementation of One Health interventions.